Managerial Analysis and Explaining the Viewpoints of the Students on Virtual Education during the COVID-19 Pandemic at the Virtual School of Medical Education and Management of Shahid Beheshti University of Medical Sciences in 2020 - Zahra Ayazi; Soleiman Ahmady (Kerman University of Medical Sciences, 2020)
Background: In the current COVID-19 crisis, the necessity for respecting social distancing and making the new decisions by officials, and the closure of universities moved the classrooms to entire online home learning. Strategic planning allows the university to adapt its activities to meet the changing needs of the environment. Objectives: The present study aimed at explaining the viewpoints of students and evaluating the phenomenon of virtual education of students during the COVID-19 pandemic in the Virtual School of Medical Education and Management of Shahid Beheshti University of Medical Sciences in the academic year 2020. Internal and external factors affecting this system  were identified and analyzed.  Methods: The present descriptive-survey described the conditions and characteristics of virtual education and surveyed students' viewpoints on factors affecting this system of education. Using the TOWS (Threats, Opportunities, Weaknesses, Strength) matrix,, the internal and external factor evaluation matrices were plotted, and the final score of each factor was achieved by determining its coefficient and rank, and proper strategy was formulated after analysis. Results: The TOWS matrix analyses showed the overtake of threats by opportunities and the exceed of strengths over weaknesses in factors affecting the virtual education, indicating the strategic status of the virtual education of the virtual school in the ST (strengths-threats) cell. Conclusion: Coronavirus outbreak is not the end of a pandemic, and there is still the risk of the emergence of other diseases and crises. The valuable experience learned from the Coronavirus era can be used in the development of virtual education in the studied and other faculties. Fortifying strengths, benefitting from opportunities, reducing weaknesses, and fixing threats can provide a suitable strategic basis for planning virtual education in Iran.